An Unusual Presentation of Streptococcus gallolyticus in Infective Endocarditis - Laura Torres Cruz; Maryam Barkhordarian; Neenu Antony; Muhammad Yasir; Sai Priyanka Pulipaka; Ahmad Al-Awwa; Sameh Elias (Case Reports in Cardiology)
Background. Streptococcus gallolyticus (previously known as Streptococcus bovis type-1) bacteremia has a well-established, almost pathognomonic association with colorectal carcinoma, with the most common hypothesized mechanism being ulceration of polyps leading to hematologic dissemination. There are few reported cases of streptococcus bacteremia from other, seemingly benign sources like cellulitis or colonic adenomas. Hence, there is limited focus on skin and soft tissue infections leading to potentially fatal infective endocarditis. Case Presentation. We present a novel case of streptococcus bacteremia from uncommon sources like abdominal wall cellulitis or colonic adenoma leading to infective endocarditis as well as other manifestations, including osteomyelitis and discitis. This report highlights a unique case of streptococcus bacteremia with an uncommon origin, arising from abdominal wall cellulitis or colonic adenoma, ultimately resulting in the development of infective endocarditis. Furthermore, the patient presented with additional clinical manifestations, including osteomyelitis and discitis. Conclusions. Through our case report, we emphasize the importance of investigating uncommon sources like cellulitis when initial malignant workup is negative in streptococcus bacteremia and further elucidate the pathophysiology of streptococcus bacterial dissemination from nonmalignancy-related sources.